TINJAUAN SURAH AL-BAQARAH 221 TERHADAP RELEVANSI PERNIKAHAN BEDA AGAMA DI INDONESIA - Bariki, Yusril; Afifah, Nur (UIN Sumatera Utara Medan, 2024)
Interfaith marriage is widely discussed and researched by kiyais or ustadz as well as scholars from various places. But none of the answers were lasting and the issues kept coming. By using the library research method or library research, it means collecting data using books or journals etc. It could be interpreted that related to interfaith marriages finds Surah Al-Baqarah: 221 that it is expressly prohibited, in the opinion that is pro-argument, that when you are not married it will have a worse impact, because you both like each other. As for the cons, they defended that in religious rules it is not permissible to marry someone who is not of the same faith.